2004
DOI: 10.1016/s0002-9440(10)63737-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor-γ Reverses Squamous Metaplasia and Induces Transitional Differentiation in Normal Human Urothelial Cells

Abstract: We observed that in urothelium, both cornifying and noncornifying forms of squamous metaplasia are accompanied by changes in the localization of the nuclear hormone receptors, peroxisome proliferator activated receptor gamma (PPAR-gamma) and retinoid X receptor (RXR-alpha). To obtain objective evidence for a role for PPAR-gamma-mediated signaling in urothelial differentiation, we examined expression of the cytokeratin isotypes CK13, CK20, and CK14 as indicators of transitional, terminal transitional, and squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 48 publications
7
101
0
2
Order By: Relevance
“…As a positive control, cytokeratin markers of transitional and terminal urothelial differentiation (CK13 and CK20, respectively) were included and confirmed our previous report (Varley et al, 2004b) that co-treatment with TZ and PD153035 resulted in upregulation of CK13 (data not shown) and de novo expression of CK20 (Fig. 4).…”
Section: Effects Of Tz and Egf Signalling On The Localisation Of Tighsupporting
confidence: 83%
See 3 more Smart Citations
“…As a positive control, cytokeratin markers of transitional and terminal urothelial differentiation (CK13 and CK20, respectively) were included and confirmed our previous report (Varley et al, 2004b) that co-treatment with TZ and PD153035 resulted in upregulation of CK13 (data not shown) and de novo expression of CK20 (Fig. 4).…”
Section: Effects Of Tz and Egf Signalling On The Localisation Of Tighsupporting
confidence: 83%
“…Increasing exogenous [Ca 2+ ] to 2 mM results in desmosome formation, but the cells do not undergo cytodifferentiation (Southgate et al, 1994;Varley et al, 2004a) and, as demonstrated above, there was no induction of claudin protein expression or claudin relocalisation to TJs. By contrast, when EGFR-mediated proliferation is blocked, activation of PPARγ initiates a sequence of events culminating in expression of the uroplakins (Varley et al, 2004a) and cytokeratin markers of terminal urothelial cytodifferentiation (Varley et al, 2004b Our study indicates that the changes in claudin expression are regulated through both transcriptional and post-translational mechanisms. It appears that claudin 3 gene expression may be transcriptionally regulated directly by PPARγ, as analysis of the claudin 3 gene promoter revealed consensus PPARγ-binding response elements (PPRE) and claudin 3 mRNA was detected within 3 days of PPARγ activation and was specifically knocked-down by PPARγ siRNA.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Lipid metabolism including arachidonic acid and PG has been implicated in these disorders (Heller et al 1998). Furthermore, involvement of PPARg has been reported in regulating lipid homeostasis, immune response, cell differentiation and cell proliferation (Heller et al 1998, Bishop-Bailey & Wray 2003, Varley et al 2004. We conclude that upregulation of AKR1C3 as reflected by an increase in immunoreactivity is associated with both neoplastic and nonneoplastic pathological changes in the prostate.…”
Section: Discussionmentioning
confidence: 70%